Allantodapsone is a Pan-Inhibitor of Staphylococcus aureus Adhesion to Fibrinogen, Loricrin, and Cytokeratin 10 - Filippo Prencipe; Aishah Alsibaee; Zainab Khaddem; Padraig Norton; Aisling M. Towell; Afnan F. M. Ali; Gerard Reid; Orla M. Fleury; Timothy J. Foster; Joan A. Geoghegan; Isabel Rozas; Marian P. Brennan (Microbiology Spectrum, 2022)
ABSTRACT Staphylococcus aureus infections have become a major challenge in health care due to increasing antibiotic resistance. We aimed to design small molecule inhibitors of S. aureus surface proteins to be developed as colonization inhibitors. We identified allantodapsone in an initial screen searching for inhibitors of clumping factors A and B (ClfA and ClfB). We used microbial adhesion assays to investigate the effect of allantodapsone on extracellular matrix protein interactions. Allantodapsone inhibited S. aureus Newman adhesion to fibrinogen with an IC50 of 21.3 μM (95% CI 4.5-102 μM), minimum adhesion inhibitory concentration (MAIC) of 100 μM (40.2 μg/mL). Additionally, allantodapsone inhibited adhesion of Lactococcus lactis strains exogenously expressing the clumping factors to fibrinogen (L. lactis ClfA, IC50 of 3.8 μM [95% CI 1.0–14.3 μM], MAIC 10 μM, 4.0 μg/mL; and L. lactis ClfB, IC50 of 11.0 μM [95% CI 0.9–13.6 μM], MAIC 33 μM, 13.3 μg/mL), indicating specific inhibition. Furthermore, the dapsone and alloxan fragments of allantodapsone did not have any inhibitory effect. Adhesion of S. aureus Newman to L2v loricrin is dependent on the expression of ClfB. Allantodapsone caused a dose dependent inhibition of S. aureus adhesion to the L2v loricrin fragment, with full inhibition at 40 μM (OD600 0.11 ± 0.01). Furthermore, recombinant ClfB protein binding to L2v loricrin was inhibited by allantodapsone (P < 0.0001). Allantodapsone also demonstrated dose dependent inhibition of S. aureus Newman adhesion to cytokeratin 10 (CK10). Allantodapsone is the first small molecule inhibitor of the S. aureus clumping factors with potential for development as a colonization inhibitor. IMPORTANCE S. aureus colonization of the nares and the skin provide a reservoir of bacteria that can be transferred to wounds that can ultimately result in systemic infections. Antibiotic resistance can make these infections difficult to treat with significant associated morbidity and mortality. We have identified and characterized a first-in-class small molecule inhibitor of the S. aureus clumping factors A and B, which has the potential to be developed further as a colonization inhibitor.